The role of life experiences in the continuation of the adult criminal career - Quinet, M. (Criminal behaviour and mental health, 1996)
This study provides an outlook on the impact that both specific life experiences and age have on criminal activity of a sample of former juvenile delinquents aged between 18 and 31. The life experiences scrutinised are marriage and family, work, incarceration and the consumption of illicit drugs. Our study aims at determining which factors, independent of the pure ageing process, play a role in the continuation or termination of a former juvenile delinquent career. Subjects were drawn from a 1970s study of 428 male delinquents. In the early 1990s, 238 of them were met for a retrospective interview. Several results of the study deserve consideration. First, the marital life of the men affects their participation in crime. Cohabitation with a mate is positively associated with crime among very young adults (18 to 21 years old), whereas it acts as a force toward desistance after the age of 21. Also, our results indicate that lawful employment acts to deter the continuation of offending. Finally, the habit of using illicit drugs impedes the social adaptation of former juvenile delinquents. In fact, drug use during adulthood is the best predictor of a continuing adult criminal career. Copyright Ř 1996 Whurr Publishers Ltd